The treatment of malignant ventricular tachycardia by aorto-coronary saphenous vein bypass graft. Issue 581 (March 1974) - Ikram, H.; Jeffery, R. M.; Parkins, R. A.; Makey, A. R.; Emery, E. R. J.; Stone, D. L.
Abstract : A 61-year-old man with a previous cardiac infarction had at least fifteen attacks of ventricular tachycardia which finally did not respond to either drug or electrical therapy. Angiography showed a blocked right coronary artery and a non-contractile portion of postero-inferior left ventricular wall. An aorto to right coronary saphenous vein bypass graft was inserted, and although attacks of tachycardia occurred following the operation these were of short duration and reverted spontaneously. He has been free of tachycardia for 5 weeks, with a greatly improved effort tolerance.